2016
DOI: 10.31051/1852.8023.v5.n1.14050
|View full text |Cite
|
Sign up to set email alerts
|

ANOMALOUS ORIGIN OF THE LEFT VERTEBRAL ARTERY. Origen anómalo de la arteria vertebral izquierda

Abstract: Las variaciones de los principales vasos arteriales son de importancia clínica. La arteria vertebral (VA) normalmente surge de la arteria subclavia. El presente informe describe un origen anómalo de la arteria vertebral izquierda (LVA) desde el arco aórtico entre el origen de la subclavia izquierda y la arteria carótida común izquierda. Esta arteria cruzó superficialmente de medial a lateral el tronco simpático izquierdo. La VA izquierda y derecha entraban en los agujeros transversos de la quinta vértebra cerv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Two of the most common variations with regard to the origin of the left vertebral artery is directly from the arch of the aorta, between the left common carotid and the left subclavian arteries, and in this study, three cadavers showed this variation. The second common variation is the left vertebral artery arising from a common trunk formed by the common carotid and vertebral arteries or subclavian and vertebral arteries [1,3,11,12,17,18,19,22,26,35]. In the case where the presence of two left vertebral arteries were observed, it was found that one originated from the aortic arch and the other from the left subclavian artery [7,16,17,24,30].…”
Section: Discussionmentioning
confidence: 99%
“…Two of the most common variations with regard to the origin of the left vertebral artery is directly from the arch of the aorta, between the left common carotid and the left subclavian arteries, and in this study, three cadavers showed this variation. The second common variation is the left vertebral artery arising from a common trunk formed by the common carotid and vertebral arteries or subclavian and vertebral arteries [1,3,11,12,17,18,19,22,26,35]. In the case where the presence of two left vertebral arteries were observed, it was found that one originated from the aortic arch and the other from the left subclavian artery [7,16,17,24,30].…”
Section: Discussionmentioning
confidence: 99%